Impacto clínico e parasitológico no tratamento a curto prazo de cães com leishmaniose visceral utilizando miltefosina e alopurinol e identificação do locus de sensibilidade a miltefosina - Ayres, Eveline da Cruz Boa Sorte (2022)
The euthanasia of dogs affected by visceral leishmaniasis (VL) is one of the measures to control the disease, but it is increasingly less tolerated by the affective bond that unites the human and canine species. And given the studies pointing out that this control strategy has not shown effectiveness in reducing human cases, canine treatment has been proposed as an alternative to the sacrifice of dogs diagnosed as positive. The objectives of this research were to treat dogs naturally infected by Leishmania infantum using miltefosine and allopurinol alone and in association, evaluating the effectiveness of the protocols by reducing clinical signs, decreasing antibody levels by indirect immunofluorescence (IFAT) and reduction of skin parasite load by qPCR in 28 days of treatment. As well as identifying the presence or deletion of the miltefosine sensitive locus (MSL) in the strains of L. infantum that infected these dogs from biological samples collected before the treatments, correlating the MSL with the reduction of clinical signs and parasite load. The results showed that the protocols with allopurinol alone (20 mg/kg/BID) and associated with miltefosine (2 mg/kg/day) significantly reduced the parasite load (p < 0.01 and p < 0.01, respectively) in the skin of positive dogs. The therapies also promoted a significant decline in clinical signs in the three groups of dogs (p < 0.01). A moderate correlation between skin parasite burden and clinical score was observed in all three treatment groups (r > 0.5). The antibody levels did not decrease in this short period. MSL was identified in 77.8% of the strains and 22.2% had a deletion. The presence of MSL was correlated with clinical improvement regardless of the therapeutic protocol instituted. However, there was a strong and positive correlation in relation to the decrease in the parasite load in dogs treated exclusively with miltefosine, however, with a decrease in the correlation in treatments with the association of miltefosine with allopurinol and allopurinol alone. It was concluded that short-term treatment with allopurinol reduced the amount of parasites on the skin of dogs with VL. However, its efficiency is enhanced when associated with miltefosine. It was also possible to detect MSL from clinical samples and that its deletion is present in L. infantum strains circulating in Cuiabá, suggesting the possibility of a natural resistance to this drug. However, research on MSL should be encouraged, as there are indications that it could become a promising marker to predict the efficacy of miltefosine leading to more efficient therapeutic strategies.